Peran Budaya Organisasi dan Motivasi Kerja dalam Meningkatkan Kinerja Karyawan (Studi Regresi Linear Berganda pada Perusahaan Bedak Obat Tradisional di Surabaya) - Supriyanto, Supriyanto; Sutejo, Bambang; Dewi, Pinky Pininta; Prakasa, Davis Febrinanto (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of organizational culture and work motivation on employee performance at a traditional medicinal powder company in Surabaya. A quantitative approach was employed using a survey method with a Likert-scale questionnaire. The sample was determined using Slovin’s formula, involving 71 randomly selected respondents. Data were analyzed through validity and reliability tests, classical assumption tests, and multiple linear regression using SPSS version 25. The results indicate that organizational culture has a positive and significant effect on employee performance. Work motivation also shows a positive and significant effect, and it is identified as the most dominant factor in improving performance. Simultaneously, organizational culture and work motivation contribute 75.9% to variations in employee performance, while the remaining 24.1% is influenced by other factors outside the research model. This study emphasizes the importance of strengthening organizational culture and enhancing work motivation to sustain employee performance in the traditional cosmetics industry.